The Potential of Sacha Inchi as a Plant-Based Milk Innovation in Contextual Learning: A Conceptual Review of Science Literacy and Nutritional Awareness - Taufik, Yusman; Widiantara, Tantan; Fathoni, Riza; Nurkanti, Mia; Erina, Sri (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This article presents a conceptual review examining the potential of Sacha Inchi–based plant milk as an innovation in contextual learning to support scientific literacy and nutritional awareness. Drawing on pedagogical and educational technology perspectives, the review synthesizes literature on contextual learning, learning resources, scientific literacy, nutrition education, and food-based innovations. Scientific literacy is positioned as a conceptual construct that develops through learners’ engagement with meaningful real-life contexts rather than as a measurable instructional outcome. The synthesis highlights a pedagogical shift from content-centred learning to context-centred learning, in which every day phenomena function as learning resources that mediate conceptual understanding. Within this framework, Sacha Inchi–based plant milk is conceptualized as an authentic and interdisciplinary learning resource connecting science, nutrition, and sustainability. The review emphasizes the role of educational technology in organizing and integrating contextual learning resources through purposeful pedagogical design. Rather than evaluating instructional effectiveness, this article offers a theoretical framework to inform instructional design, curriculum development, and future research in contextual and technology-supported education.